2023
DOI: 10.3389/fvets.2022.1066048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the bacterial communities in chromium-contaminated soils

Abstract: IntroductionHexavalent chromium or Cr(VI) is essential to various industries, such as leather manufacturing and stainless steel production. Given that inevitable leakage from industries pollutes the soil and thereby affects the soil environment. Microbial communities could improve the quality of the soil. Abundant bacterial communities would significantly enhance the soil richness and resist external pressure, benefiting agriculture. But the pollution of heavy metal broke the balance and decrease the abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The contamination of Cr in soils has been shown to significantly impact the composition of bacterial communities. Zhu et al (2023) [ 6 ] demonstrated that chromium contamination induces alterations in bacterial communities inhabiting the CS. Specifically, the presence of Cr can impact the richness and variety of bacterial taxa, including Firmicutes and Acidobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of Cr in soils has been shown to significantly impact the composition of bacterial communities. Zhu et al (2023) [ 6 ] demonstrated that chromium contamination induces alterations in bacterial communities inhabiting the CS. Specifically, the presence of Cr can impact the richness and variety of bacterial taxa, including Firmicutes and Acidobacteria.…”
Section: Introductionmentioning
confidence: 99%